2007
DOI: 10.1002/chin.200737155
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Study of Biological Activity of Some New 1,4‐Benzothiazines.

Abstract: Compounds (I) and (XIII) show highly promising antifungal effects against Aspergillus niger. The activity of (XIII) is co-related with the NH-NH2 group at position-3. -(DESHMUKH*, M. B.; DESHMUKH, S. A.; JAGTAP, S. S.; MULIK, A. R.; Indian J. Chem., Sect. B: Org. Chem. Incl. Med. Chem. 46 (2007) 5, 852-859; Dep. Chem., Shivaji Univ., Kolhapur 416 004, India; Eng.) -A. Forchert 37-155

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The 1,2-benzothiazines have shown various biological activities such as anti-inflammatory [9], CNS depressant [10,11], anti-depressants [12], anticancer [13] and antimicrobial [14]. They also act as potent calpain I inhibitors [15] and vasodilators [16]. Previous research has shown 1,2-benzothiazines to be potent antimicrobial agents against Gram-positive bacterial strains and fungal strains such as Aspergillus flavus , Aspergillus niger , Fusarium oxysporum [17].…”
Section: Introductionmentioning
confidence: 99%
“…The 1,2-benzothiazines have shown various biological activities such as anti-inflammatory [9], CNS depressant [10,11], anti-depressants [12], anticancer [13] and antimicrobial [14]. They also act as potent calpain I inhibitors [15] and vasodilators [16]. Previous research has shown 1,2-benzothiazines to be potent antimicrobial agents against Gram-positive bacterial strains and fungal strains such as Aspergillus flavus , Aspergillus niger , Fusarium oxysporum [17].…”
Section: Introductionmentioning
confidence: 99%